2017
DOI: 10.4236/ojbm.2017.51008
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Career Growth and Job Engagement among Young Employees: The Mediating Role of Normative Commitment and the Moderating Role of Organizational Justice

Abstract: With the sharp changes in external environment, sustainable competitive advantage is importance resource that the enterprises need to get in the fierce market game. The 90's are becoming the backbone of enterprises, and under the background of human resources, driving the development of the enterprise innovation ability by cultivating highly professional knowledge staff is the important measure of enterprise to obtain sustainable competitive advantage. This study will explore the relationship between employees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…With career development carried out regularly in the Bukittinggi City Government environment, employees are proud of the work they do. Further research conducted by Bai & Liu (2018) and Liu, He, & Yu (2017) revealed that career development had a significant effect on employee engagement.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…With career development carried out regularly in the Bukittinggi City Government environment, employees are proud of the work they do. Further research conducted by Bai & Liu (2018) and Liu, He, & Yu (2017) revealed that career development had a significant effect on employee engagement.…”
Section: Resultsmentioning
confidence: 97%
“…Specifically, the mediating role of work involvement in the relationship between the intrinsic function of organizational career growth and career commitment is stronger when employees perceive their leaders as role models. Further research conducted by (Bai & Liu, 2018) and Liu, He, & Yu (2017) revealed that career development significantly affected employee engagement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Promotions are one of the talent management practices because they are sometimes done to place people with good credentials into specific jobs in an effort to broaden their skills (Ruderman and Ohlott, 1994). Studies (Anitha, 2014;Bai and Liu, 2018;Khan and Altaf, 2015;Liu et al, 2017;Meijerink et al, 2018;Saks, 2006) have related promotion and work engagement. Anitha (2014) established that career development which involves employee promotion was a predictor of work engagement of employees of small scale industries in India.…”
Section: Promotion and Work Engagementmentioning
confidence: 99%